1981
DOI: 10.1002/bjs.1800680714
|View full text |Cite
|
Sign up to set email alerts
|

Dacron graft erosion of the duodenum: A complication of interposition mesocaval shunt operations

Abstract: Two cases are reported of patients presenting with septicaemia as a late complication of a Dacron interposition mesocaval shunt operation. In both cases the prosthesis had eroded through the duodenal wall and the Dacron was in direct contact with intestinal contents. One patient died and the diagnosis was only made at postmortem examination. The other patient recovered after the problem had been recognized and treated surgically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Osborne et al reported two cases of Dacron graft erosion of duodenum after mesocaval shunt operations [10]. Martin et al reported a case of aortoesophageal fistula after repair of a descending thoracic aortic aneurysm with a Dacron interposition graft [11].…”
Section: Discussionmentioning
confidence: 98%
“…Osborne et al reported two cases of Dacron graft erosion of duodenum after mesocaval shunt operations [10]. Martin et al reported a case of aortoesophageal fistula after repair of a descending thoracic aortic aneurysm with a Dacron interposition graft [11].…”
Section: Discussionmentioning
confidence: 98%
“…In one patient erosion of the Dacron graft into the duodenum caused a persistent septicaemia. Endoscopy following a haematemesis demonstrated the cause, and the patient recovered following removal of the shunt and closure of the vascular and duodenal defects (4).…”
Section: Complications and Problemsmentioning
confidence: 93%
“…One of the complications of these prosthetic devices is intragastric migration, usually called band migration [7][8][9][10]. Symptoms associated with intragastric band migration are retrograde port infection, loss of satiety, and stop of weight loss.…”
Section: Introductionmentioning
confidence: 99%